Sinar Laser Mainan Sebagai Alternatif Sumbar cahaya Monokromatik Praktikum Kisi Difraksi Cahaya - M. Yasin Kholifudin (Jurnal Penelitian Pembelajaran Fisika, 2017)
Learning Physics on the diffraction of light through a practical on diffraction learning material using a toy laser beam as the source of monochromatic light has the obyectives to know the wavelength of a toy laser beam  and to improve  students’ learning activities. The practical was conducted in groups consisting of 10 groups each of which consists of 3 students of Senior High School 2 Kebumen in class XII ScienceA, 2014/2015 school year. The conclusions from the data analyses and observations during the learning process are; the wavelength range of the toy laser beam is on average 649 nm - 662 nm, and the laser beam as the source of monochromatic light on the diffraction learning material shoured the same monochromatic light on the screen. The student’s learning activity showed an increasing tendency indicated their active involvement in the learning process when stringing tools, observing, recording, data process, concluding and reporting their practicals. Based on the illustration mentioned above, it can be concluded that the toy laser beam can be used as an alternative source of monochromatic light which is afordable and obtainable for the teaching of  light diffraction throngh practical